Antibiotics Self Medication among Children: A Systematic Review - Fabrizio Bert; Christian Previti; Francesco Calabrese; Giacomo Scaioli; Roberta Siliquini (MDPI AG, 2022)
The phenomenon of bacterial antimicrobial resistance (AMR) is a rapidly growing global problem. Overuse and misuse of antibiotics as well as self-prescription are among the most important causes contributing to the growth of antibiotic resistance in humans. This systematic review describes the phenomenon of antibiotics self-medication (ASM) in children. The study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist by searching PubMed, Scopus, and Web of Science until July 2022. Published English language studies containing information regarding parents knowledge, attitudes, and behaviors in self-administration of antibiotics in children were included. A total of 702 articles were identified, and 57 were selected. A higher prevalence of ASM among children was found in the Middle-East (34%), Africa (22%), Asia (20%) and South America (17%), while the lowest prevalence was found in Europe (8%). High distance from hospital, and low income, such as having more than one child, are related with an increased risk of ASM in children. Fever and cough can also promote the misuse of antibiotics by parents. A greater attention to the regulation of the sale of antimicrobial drugs can certainly limit the risk of self-medicating behavior.